IMPLEMENTASI MEDIA ONLINE (WEBSITE) SEBAGAI PUBLIKASI POTENSI DESA SIDODADI MELALUI PEMBERDAYAAN KARANG TARUNA - Ahsan, Moh; Aziz, Abdul (Universitas Muhammadiyah Tapanuli Selatan, 2018)
Sidodadi Village is one of the villages located in southern Malang area located in Gedangan sub-district. The village is one of the villages that has the most extraordinary natural potentials such as Ungapan Beach, Bajulmati Beach, Parangdowo Beach, Jolangkung Beach, Bengkung Beach, Ngudel Beach, and Ngantep Beach, which is a beach located in the southern cross of Malang Regency. Rows of mountains are sturdy and beautiful to make the tourists interested to travel there.Sidodadi village area bounded with Sumbermanjing wetan district in the east, village elephant rejo in the west. On the other hand, not only the potential of nature is extraordinary, but the results of the abundant earth. Rice, corn, coconut, banana, rice, cassava, mangosteen, durian, and palm are natural products that can be processed there. The potential possessed and remarkable until now has not been published or promoted through websites and social media, to hog the visitors who more aplagi most visitors see the first reference before coming directly.The abundant natural resources with the stammered human resources of technology will make the potential of nature unknown to the wider community. Coral cadets and devices in the village of Sidodadi maximal educated High School (SMA) and only two people who can take the bench lecture. This is where the turmoil experienced by villagers Sidodadi where they can not publish the area. Only limited to the beaches that have been published, but for other natural potentials can not be published because of lack of knowledge about the use of the internet (Online Media).Â Keywords:Sidodadi, Karangtaruna, Publikasi, Online.